If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -71 + 10x = -10x + -55 Reorder the terms: -71 + 10x = -55 + -10x Solving -71 + 10x = -55 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. -71 + 10x + 10x = -55 + -10x + 10x Combine like terms: 10x + 10x = 20x -71 + 20x = -55 + -10x + 10x Combine like terms: -10x + 10x = 0 -71 + 20x = -55 + 0 -71 + 20x = -55 Add '71' to each side of the equation. -71 + 71 + 20x = -55 + 71 Combine like terms: -71 + 71 = 0 0 + 20x = -55 + 71 20x = -55 + 71 Combine like terms: -55 + 71 = 16 20x = 16 Divide each side by '20'. x = 0.8 Simplifying x = 0.8
| 8(3ax+y)=23ax-7y | | 5x-3x+5ifx=2 | | 1.1x-9=0.7x-31 | | 18t^2+45t-500=0 | | 18h+125=12h+200 | | 5x-(-0.2)+4=11 | | 104-8x=204+4x | | x^2+6x+9=121 | | 4z^2=49 | | 9.3-4x=-2.3-2x | | 0.5(a+3)+8.75=13.25 | | 3y+8=41 | | 4/(5x+2)=6/(x-1) | | 3.5-2x=9.1-7x | | -11+2x=3x-47 | | 4/(5x-2)=6/(x-1) | | (3x+5)(2x-9)=0 | | (3X+7/2X+4)=3/4 | | y=-2(-0.999)+2 | | -11=25-4z | | 7M+13=M+7 | | x=2*(3-y) | | 8z^2+cz+34=(4z+5)(2z+7) | | -9x-46=-32-5x | | (3/4)x+3=11 | | 2x=78.45 | | 10(3+a)=60 | | -(5-(3-g))= | | 30000/733.2= | | 4/(5x-7)=6/(x-1) | | 2(23+a)=34 | | 2x+36=50 |